Investigating strangeness enhancement in jet and medium via 𝜙⁡(1020) production in 𝑝-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Menzel, Marius; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; Schlepper, Felix; et al. (Physical review, 2024)
This work aims to differentiate strangeness produced from hard processes (jetlike) and softer processes (underlying event) by measuring the angular correlation between a high-momentum trigger hadron (ℎ) acting as a jet proxy and a produced strange hadron [𝜙⁡(1020) meson]. Measuring ℎ−𝜙 correlations at midrapidity in 𝑝-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV as a function of event multiplicity provides insight into the microscopic origin of strangeness enhancement in small collision systems. The jetlike and the underlying-event-like strangeness production are investigated as a function of event multiplicity. They are also compared between a lower and higher momentum region. The evolutions of the per-trigger yields within the near-side (aligned with the trigger hadron) and away-side (in the opposite direction of the trigger hadron) jets are studied separately, allowing for the characterization of two distinct jetlike production regimes. Furthermore, the ℎ−𝜙 correlations within the underlying event give access to a production regime dominated by soft production processes, which can be compared directly to the in-jet production. Comparisons between ℎ−𝜙 and dihadron correlations show that the observed strangeness enhancement is largely driven by the underlying event, where the 𝜙/ℎ ratio is significantly larger than within the jet regions. As multiplicity increases, the fraction of the total 𝜙⁡(1020) yield coming from jets decreases compared to the underlying event production, leading to high-multiplicity events being dominated by the increased strangeness production from the underlying event.
Im Titel steht der Ausdruck sNN unter dem Wurzelsymbol, NN ist dabei tiefgestellt
Gesehen am 14.01.2026
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, V.J.G. Feuillard, I. Fokin, P. Glässel, M.W. Menzel, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, F. Zanone [und zahlreiche weitere]